Nicotinamide complex of silver(III) with expanded coordination number. Issue 11 (3rd July 2018) - Sun, Yunfu; Kirschenbaum, Louis J.
Abstract: In strongly alkaline media ([OH − ] ≥ 0.12 M), nicotinamide (nica ) forms a complex with square-planar Ag(OH)4 − [nica] ≥ 0.05 M. The complex decomposes in seconds to nicotinamide N-oxide. The correlation of maximum absorbance of the complex with concentrations of nicotinamide and hydroxide requires that the complex is either the five-coordinate Ag(OH)4 (H-1 nica ) 2− or the six-coordinate Ag(OH)5 (nica ) 2− . Comparison with the reactions of Ag(OH)4 − with nicotinate ion (nic − ) and acetamide under similar conditions indicates that nicotinamide coordinates with Ag(OH)4 − by the amido group rather than the nitrogen on the pyridine ring or the amido oxygen. Kinetics of the Ag(III)-nica redox reaction are consistent with direct reaction between nicotinamide and uncoordinated Ag(OH4 ) − . Oxidation takes place at the pyridine ring, yielding nicotinamide N-oxide. Silver(III) is reduced to monovalent silver. Graphical Abstract: